0257 Age-related Differences in Sleep Spindles and Their Association with Episodic Memory in Adolescents. (27th April 2018) - Goldstone, A; Willoughby, A R; de Zambotti, M; Franzen, P L; Sullivan, E V; Kardos, L M; Claudatos, S A; Rosas, L; Alschuler, V R; Lim, Y; Gil, M; Hasler, B P; et al.
Abstract: Introduction: Specific sleep features, such as sleep spindles, are implicated in memory processing. Although changes to both cognitive ability and sleep architecture occur during adolescence, little is known about developmental changes to sleep spindles and how such changes may be related to cognition. Here we investigated age- and sex-related differences in sleep spindle characteristics and whether sleep spindles were associated with memory ability. Methods: 133 adolescents, aged 12–21 years ( M =15.55), from the National Consortium on Alcohol and NeuroDevelopment in Adolescence (NCANDA) study, were included in this cross-sectional analysis of baseline polysomnographic (PSG), electroencephalographic (EEG) and cognitive data. Semi-automatic detection of fast sleep spindles (~13Hz) across central electrodes was conducted using custom MATLAB code. Average density, amplitude, duration and sigma power were then calculated for each participant. Participants also completed a number of cognitive tasks, within three months of their overnight recordings, of which we focused on a subset of memory tasks from the WebCNP battery (webcnp.med.upenn.edu/battery). Results: Older age was associated with greater spindle density (β=0.24), lower sigma power (β=-0.39), smaller spindle amplitude (β=-0.43) and shorter spindle duration (β=-0.26). No significant differences in spindle characteristics between sexes were identified. Greater spindle density was associated with better delayed performance on the Short Visual Object Learning Task (i.e. number of shapes remembered following an ~25-minute delay after the initial presentation and recall of the shapes) (β=0.26). Spindle characteristics were not associated with general cognitive abilities. Conclusion: Moderate age-related differences in spindle characteristics were identified in this sample of adolescents. We also identified an association between spindle density and performance on an episodic, visual learning task, despite the fact that cognitive testing did not necessarily occur in immediate proximity to the sleep EEG recording. This suggests that the relationship between sleep spindles and cognition may reflect more than memory consolidation. For example, spindle density may be a marker of an individual's learning capacity or may reflect the maturity of certain brain networks which support learning ability. Support (If Any): AA021690 (DBC) and AA021696 (IMC+FCB).